The Gambia : Poverty Reduction Strategy Paper; Annual Progress Report. (IMF Staff Country Reports; Country Report, 2009)
The paper presents the Annual Progress report on The Gambia's Poverty Reduction Strategy Paper. This has enabled the government to substantially reduce the stock of domestic arrears that have been due to contractors, consultants, and suppliers and at the same time liquidate all loans owed to the Parastatals. The dalasi has been appreciated by 32 percent in the later part of the third quarter of 2007, which helped to reduce dalasi payments against debt service obligations and other international payment obligations.